Governance by comparison: How ratings & rankings impact national policy-making in education - Kerstin Martens; Dennis Niemann (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2010)
How can international comparisons have an impact on one country while others are not affected at all? This paper examines the power of ratings & rakings (R&R) using the example of the OECD's PISA study (Programme for International Student Assessment) and its differential impact on national education policy making. We argue that R&R have an impact if the evaluated topic is framed as crucial for national objectives and if, at the same time, a substantial gap between national self-perception and the empirical results can be observed. After assessing the media impact of PISA on 22 OECD countries, we illustrate our theoretical argument through the use of examples of two poorly performing countries who demonstrated entirely opposite reactions: Germany and the U.S. While the German system of secondary education was strongly affected by the international comparison and underwent comprehensive changes, the U.S. did not respond to its below-average ranking at all. The theoretical concepts of self-perception and framing offer explanatory power to delineate the different reaction patterns. – – Wie kommt es, dass internationale Vergleichsstudien bestimmte Staaten substantiell beeinflussen andere jedoch nicht? Am Beispiel der OECD PISA-Studie untersucht dieses Arbeitspapier den Einfluss von Rankings und Ratings (R&R) auf nationale Bildungspolitiken. Wir argumentieren, dass R&R besonders dann einen Einfluss entfalten, wenn der evaluierte Gegenstand zum einen als entscheidender Politikbereich verstanden wird und wenn gleichzeitig eine Diskrepanz zwischen nationaler Selbstwahrnehmung und empirisch erzieltem Ergebnis besteht. Nach Darstellung der Medienreaktionen in 22 OECD-Ländern wird unsere Argumentation am Beispiel von zwei gegensätzlich reagierenden Ländern illustriert: Deutschland und den USA. Während in Deutschland die negativen PISA-Ergebnisse zu einem umfassenden Bildungsdiskurs und zu massiven Bildungsreformen geführt haben, zeigten die USA keine öffentliche oder gar politische Reaktion auf ihre ebenfalls negativen Resultate.
Keywords: 330; Bildungsniveau; Bewertung; International; Bildungspolitik; Öffentliche Meinung; Wahrnehmung; OECD-Staaten